Causes and risk factors of maternal deaths in Namibia (Journal for Studies in Humanities and Social Sciences, 2014)
The main purpose of this paper was to identify causes of maternal deaths in all districts and referral hospitals, and to assess risk factors and determine underlying contributory factors to maternal deaths in Namibia. The study proposed strategies for midwifery practice in order to prevent maternal deaths. A retrospective audit of maternal records was conducted with detailed analysis of the 154 maternal deaths recorded during the period 2008-2012. Of the 154 maternal deaths reviewed, 58.4% were from direct maternal deaths and 41.6% were from indirect maternal deaths. Hemorrhage (37.8%), eclampsia (24.4%) and puerperal sepsis (23.3%) were the leading causes for direct maternal deaths. About 65% of the hemorrhage cases; 64% of the eclampsia cases and 53% of the puerperal sepsis occurred to women who lived in rural areas. The predominant recognizable indirect causes were HIV (45.3%); pneumonia (23.4%) and Tuberculosis (17.2%). Women who live in rural areas were more likely to experience a maternal death due to pneumonia (60%) as compared to those in urban areas. Most women who died due to HIV were aged between 30-39 years (75.9%) while maternal deaths due to eclampsia were most common among the younger women (15-29 years). Maternal deaths are less likely to occur to women living together with their partner than those who are not living together (OR = 0.53). This descriptive study identified a range of socio demographic, clinical and health system factors as possible contributors to maternal deaths in Namibia